Fundamentals of Geriatric Medicine A Case-Based Approach - Soriano, Rainier P.; Soriano, Rainier P. (Springer New York : Imprint: Springer, 2007)
As the population ages, the unique needs of elderly patients are becoming increasingly important to practitioners of primary care, geriatric medicine, family medicine, and internal medicine. Physicians need a handy resource that presents the essentials of geriatric medicine and suggests simple ways to provide better care. Experts in geriatric medicine have streamlined Cassel’s classic text, Geriatric Medicine: An Evidence-Based Approach, Fourth Edition, into this concise guide filled with focused information and case-based instruction. This handbook addresses the complexity of disease prevention and presentation in elderly patients, as well as geriatric pharmacology. Medicare and Medicaid, and conditions common to elderly patients, including depression, dementia, and hypertension, are also covered. Numerous graphs and tables are included throughout the book to assist the reader in processing the information presented and incorporating it into clinical practice. This practical guide is an essential resource for all those caring for the elderly.